Slip surface identification using electrical resistivity tomography for landslide hazard management in degraded land: A case study from Tabbinjai, South Sulawesi - Mallarangeng, Nurjinaan Fakri A.; Busthan, Busthan; Sultan, Sultan (Brawijaya University, 2026)
Gowa Regency, South Sulawesi Province, has long been subject to recurrent shallow landslides, degrading its hillslopes by removing productive topsoil, disrupting drainage systems, and threatening the livelihoods of local communities. But no meaningful land rehabilitation effort can be carried out unless what is underneath these unstable slopes is known. This was the first subsurface investigation in this region. This study fills the gap by applying two-dimensional Electrical Resistivity Tomography (ERT) with the Wenner-Schlumberger array configuration in three survey profiles to identify and map the slip surfaces controlling the slope failure. The data were inverted using RES2DINV software to obtain 2D models of the subsurface resistivity. All profiles show a similar three-layered subsoil structure: a shallow clay-rich layer (1-15 ?m), a weathered tuff layer (30-50 ?m) at a depth of 5-7 m, which is the main slip surface, and competent volcanic bedrock of breccia and basalt (100-250 ?m) at the surface. When saturated, the weathered tuff loses shear strength dramatically, driving translational landslides that have repeatedly degraded this landscape. The robustness of these results is supported by subsequent landslip events at the investigated sites, with failure behavior consistent with the subsurface model derived from the ERT. The results provide a concrete spatial foundation for prioritizing subsurface drainage, slope revegetation, and land-use zoning as integrated strategies for the rehabilitation of landslide-degraded land in Tabbinjai.